Protective Effect of Virgin Coconut Oil on Cyclophosphamide-induced Histological Changes in Lymphoid Tissues - Senin, Mu’izuddin M.; Al-Ani, Imad M.; Mahmud, Mohamed Imad A. M.; Muhammad, Naznin; Kasmuri, Hanif M. (IIUM Medical Journal Malaysia, 2018)
Introduction: Virgin coconut oil (VCO) is known for its health and therapeutic benefits. However, the immunomodulatory effects of VCO have not been extensively investigated. Objective: The present study was devoted to examining the effects of VCO on cyclophosphamide (CY)-induced toxicity of lymphoid tissues. Methods: Thirty healthy male Wistar rats were sorted into 5 groups of 6 animals. The first control (NC) group was given distilled water via gavage at 5 ml/kg once daily. The second (CY) group received CY orally at 10 mg/kg/day for 4 weeks. Rats in the other three groups (CV5, CV10, and CV15) were given 10 mg/kg/day CY for 4 weeks, 5 m/kg/day, 10 ml/kg/day and 15 ml/kg/day VCO for 6 weeks, respectively. Rats were sacrificed at the end of 6th week; blood sample from the animals was collected for full blood count and biochemical analysis. The thymus and spleen of each animal was processed for histological examination. Results: The thymus and spleen showed marked reduction in lymphoid cellularity following daily administration of CY. The thymus also showed a marked reduction in the size of the medulla, and the white pulp areas of spleen had reduction in the follicle number and size. Supplementation with 10 ml/kg and 15 ml/kg VCO showed evidence of restoration of both the thymus and splenic lymphoid architecture. The total white cell counts, absolute lymphocyte counts and plasma globulin levels of the VCO groups were significantly increased compared to CY group. Conclusion: VCO displayed potential protective effects on CYinduced histological changes in lymphoid tissues.